2019
DOI: 10.1155/2019/2641959
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling and Larval Control of Erythrina variegata Methanol Fraction against Malarial and Filarial Vector

Abstract: Erythrina variegata (E. variegata) bioactive chemical has been the potential to be utilized as a good, eco-friendly approach for the control of mosquito population. In the present investigation, methanol extract using insecticidal compounds isolated against mosquito larvae kill assay was carried out. Secondary metabolism was characterized by thin layer chromatography, column chromatography, Fourier transform-infrared spectroscopy, gas chromatography-mass spectral, and identification of compound. Mosquito immat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…(also known as Chichinguaste) of family Lamiaceae by means of repeated preparative thin layer and column chromatography by using five-step petroleum ether and ethyl acetate elution system (5% < 10% < 20% < 40% and finally 100% ethyl acetate in petroleum ether) and detected TLC plates by anisaldehyde reagent. Recently, Baranitharan et al, (2019) 13 have also reported the phytochemical analysis of Erythrina variegata and observed the efficacy of Erythrina variegata methanol extract purified fraction against malarial and filarial vector and their results were found to be very similar to the results obtained in the present study as shown in Table 4.…”
Section: Fig 3: Mosquito Larvicidal Efficacy Of 10%-100% Concentratisupporting
confidence: 88%
“…(also known as Chichinguaste) of family Lamiaceae by means of repeated preparative thin layer and column chromatography by using five-step petroleum ether and ethyl acetate elution system (5% < 10% < 20% < 40% and finally 100% ethyl acetate in petroleum ether) and detected TLC plates by anisaldehyde reagent. Recently, Baranitharan et al, (2019) 13 have also reported the phytochemical analysis of Erythrina variegata and observed the efficacy of Erythrina variegata methanol extract purified fraction against malarial and filarial vector and their results were found to be very similar to the results obtained in the present study as shown in Table 4.…”
Section: Fig 3: Mosquito Larvicidal Efficacy Of 10%-100% Concentratisupporting
confidence: 88%
“…To improve the signal to noise ratio, the sample was then scanned 16 times for transmittance between 4000 and 400 cm − 1 (the mid-IR region). Each peak in the infrared spectrum was printed along with a label indicating its matching wavelength (Baranitharan et al 2019).…”
Section: Ftir Spectra Analysis Mle-m Maderaspatanamentioning
confidence: 99%
“…Mosquito and mosquito-borne diseases (MBDs) are successfully spreading throughout the entire world, with an inordinate impact on adolescents and children, which are more important responsible for significant global morbidity and mortality [1]. The insect-borne disease is at risk of developing worldwide following globalization and the enlargement of travel and trade from areas colonized by vectors.…”
Section: Introductionmentioning
confidence: 99%